Програмний модуль автоматизації роботи з платіжними документами для малого та середнього бізнесу - Петроченков, П. М. (ХНУРЕ, 2021)
Automation of accounting records takes a leading position among the tasks in today's enterprises. The importance of this process is conditioned by increasing the productivity of accountants and reducing the time spent on obtaining necessary information. In my opinion, nowadays small and mediumsized businesses need a new program for working with payment orders. Program module will help you without any effort to process the received order and, if necessary, to form a new payment order. All important documents will always be with you. Simple and handy program for working with payment documents is what I offer you.
Науковий керівник – ст. викл. Широкопетлєва М.С.
Keywords: ведення документації; програмний модуль; автоматизації роботи з платіжними документами